Post-mortem feasibility of dual-energy computed tomography in the detection of bone edema-like lesions in the equine foot: a proof of concept - Germonpré, Jolien; Vandekerckhove, Louis M. J.; Raes, Els; Chiers, Koen; Jans, Lennart; Vanderperren, Katrien (Frontiers in Veterinary Science, 2024)
Introduction: In this proof-of-concept study, the post-mortem feasibility of dual-energy computed tomography (DECT) in the detection of bone edema-like lesions in the equine foot is described in agreement with the golden standard imaging technique, magnetic resonance imaging (MRI). Methods: Five equine cadaver feet were studied, of which two were pathological and three were within normal limits and served as reference. Low-field MRI was performed of the foot using multiplanar MRI, followed by a DECT acquisition. Multiplanar reformations of the DECT virtual non-calcium images were compared to MRI for the detection of bone edema-like lesions. Gross post-mortem was performed and histopathologic samples were obtained of the navicular and/or distal phalanx of the two feet selected based on pathology and one reference foot. Results: On DECT virtual-non-calcium imaging, both feet selected based on pathology showed bone abnormalities as diffuse increased attenuation corresponding with bone edema-like lesions, whereas the three reference feet were considered normal. These findings were in agreement with the findings on MRI. Histopathology of the two pathologic feet showed abnormalities in line with bone edema-like lesions. Histopathology of the reference foot was normal. Conclusion: DECT virtual-non-calcium can be a valuable diagnostic tool in the diagnosis of bone edema-like lesions in the equine foot. Further examination of DECT in equine diagnostic imaging is warranted in a larger cohort, different locations, and alive animals.